2018
DOI: 10.1016/j.jneuroim.2018.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Controllable and uncontrollable stress differentially impact pathogenicity and survival in a mouse model of viral encephalitis

Abstract: Intranasal instillation of vesicular stomatitis virus (VSV) into mice given controllable stress (modeled by escapable foot shock, ES) resulted in enhanced pathogenicity and decreased survival relative to infected mice given uncontrollable stress (modeled by inescapable foot shock, IS) and non-shocked control mice. Survival likely reflected differential cytokine gene expression that may have been regulated by miR146a, a predicted stress-responsive upstream regulator. Controllability also enhanced the accumulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 75 publications
2
8
0
Order By: Relevance
“…Our results also suggest that perceived control did not detectably influence inflammatory marker levels, which may seem contrary to the pathological stress model. However, prior work has illustrated that perceived control may activate adaptive immune pathways that alter the effect of chronic stress and inflammation or the duration of acute inflammatory responses but not necessarily the magnitude of basal proinflammatory activity ( Koolhaas et al., 2011 ; Ciavarra et al., 2018 ), suggesting perceived control may be impacting outcomes through a separable mechanism. Unfortunately, we did not have data on adaptive immune markers, or multiple measurements of inflammatory markers in response to stress manipulations to test these potential hypotheses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results also suggest that perceived control did not detectably influence inflammatory marker levels, which may seem contrary to the pathological stress model. However, prior work has illustrated that perceived control may activate adaptive immune pathways that alter the effect of chronic stress and inflammation or the duration of acute inflammatory responses but not necessarily the magnitude of basal proinflammatory activity ( Koolhaas et al., 2011 ; Ciavarra et al., 2018 ), suggesting perceived control may be impacting outcomes through a separable mechanism. Unfortunately, we did not have data on adaptive immune markers, or multiple measurements of inflammatory markers in response to stress manipulations to test these potential hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…In rodents, stressor controllability reduces the duration, although not the magnitude of SNS response to environmental stressors ( Koolhaas et al., 2011 ), minimizing the chronicity of heightened arousal and associated immune response. Controllable versus uncontrollable shock also leads to greater accumulation of adaptive immune cells during injury or pathogen exposure ( Ciavarra et al., 2018 ). These cells increase the expression of brain-derived neurotrophic factors (BDNF), which may protect against inflammation-related excitotoxicity ( Yang et al., 2015 ; Kerschensteiner et al., 1999 ), and reduce susceptibility to depressive behaviors ( Banasr et al., 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our lab has found that ES and IS produce differential activation of the immune system ( Ciavarra et al, 2018 ). Pro-inflammatory cytokines released by microglia, endothelial cells, and macrophages in response to stress may alter fear memory, e.g., IL-1β administered intracerebroventricularly after shock training heightened fear memory in rats ( Song et al, 2003 ), while blocking the IL-1 receptor in mice decreased perceived anxiety-type behavior ( Wohleb et al, 2014a , Wohleb et al, 2014b ).…”
Section: Stress and Fear Memorymentioning
confidence: 99%
“…The differences in immune response induced by IS and ES can be functionally significant. This is illustrated by the fact that ongoing training with ES can dramatically increase morbidity and mortality ( Ciavarra et al, 2018 ) after intranasal inoculation of vesicular stomatitis virus, a member of the Rhaboviridae virus family, and a well-established mouse model of acute viral encephalitis ( Huneycutt et al, 1993 , 1994 ; Bi et al, 1995 ). This may seem odd given the putative beneficial effect of reducing neuroinflammation; however, it is consistent with findings that inhibitors of pro-inflammatory cytokines (antibodies, soluble receptors, and anti-inflammatory cytokines) can lead to rapid and overwhelming infection and excess mortality in models utilizing localized infection ( Opal et al, 1996 ).…”
Section: Stress and Fear Memorymentioning
confidence: 99%
“…For example, in rodents, control over stressors reduces the duration, although not the magnitude of SNS and hypothalamic pituitary adrenal-axis response to environmental stressors (Koolhaas et al, 2011), minimizing the chronicity of heightened arousal, and associated immune and metabolic costs. At the biological level, controllable versus uncontrollable shock leads to greater accumulation of adaptive immune cells during injury or pathogen exposure (Ciavarra et al, 2018). These cells increase the expression of brain-derived neurotrophic factors (BDNF), which may protect against inflammation-related excitotoxicity (Yang, Shirayama, Zhang, Ren, & Hashimoto, 2015;Kerschensteiner et al, 1999), and reduce susceptibility to depressive behaviors (Banasr, Dwyer, & Duman, 2011).…”
Section: Introductionmentioning
confidence: 99%